Pengaruh Laboratorium Virtual dalam Kegiatan Praktikum Terhadap Keterampilan Laboratorium Siswa pada Materi Titrasi Asam Basa - Iftitah Hauriyah; Muhab, Sukro; Hadinugrahaningsih, Tritiyatma (LPPM Universitas Negeri Jakarta, 2019)
This research aims to determine the effect of virtual laboratory on student laboratory skills on acid-base titration in SMAN 26 Jakarta. The subject of this study was XI IPA 1 as control group and XI IPA 3 as experiment group and was conducted on February through March 2019. The method that used in this research is quasi experiment with posttest only control group design. The sample was chosen by purposive sampling technique. The experiment group uses virtual laboratory in practical activities, while the control group uses assistance in practical activities. The result showed that the average score of the posttest in experiment group was 80.77 while the control group is 67.04. Meanwhile, the result of t-test shows that tobtined was 6,625 > ttable was 1,67. It means there is a difference on student’s laboratory skills between the experiment group and control group. Therefore, it can be conclude that the virtual laboratory in practical activities has a positive effect on student’s laboratory skills on acid base titration. Keywords Virtual laboratory, Laboratory skills, Acid base titration